2021
DOI: 10.1128/msystems.00083-21
|View full text |Cite
|
Sign up to set email alerts
|

Limited and Strain-Specific Transcriptional and Growth Responses to Acquisition of a Multidrug Resistance Plasmid in Genetically Diverse Escherichia coli Lineages

Abstract: Plasmids play a key role in bacterial evolution by transferring adaptive functions between lineages that often enable invasion of new niches, including driving the spread of antibiotic resistance genes. Fitness costs of plasmid acquisition arising from the disruption of cellular processes could limit the spread of multidrug resistance plasmids.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…First, it is rarely confirmed that the plasmid-carrying transconjugants have not acquired other chromosomal mutations that may alter chromosomal transcription independently of the plasmid. This could be determined by curing the plasmid and confirming that transcription returns to wild-type levels, or by genome sequencing the transconjugant to confirm no additional mutations are present [ 28 ]. More studies with these additional controls would be valuable.…”
Section: What Is the ‘Omic’ Footprint Of Plasmid Acquisition Upon The Host Cell?mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is rarely confirmed that the plasmid-carrying transconjugants have not acquired other chromosomal mutations that may alter chromosomal transcription independently of the plasmid. This could be determined by curing the plasmid and confirming that transcription returns to wild-type levels, or by genome sequencing the transconjugant to confirm no additional mutations are present [ 28 ]. More studies with these additional controls would be valuable.…”
Section: What Is the ‘Omic’ Footprint Of Plasmid Acquisition Upon The Host Cell?mentioning
confidence: 99%
“…carbohydrate, energy, amino acid), with the direction of regulation often varying among bacterium–plasmid pairings, sometimes for the same functional group of genes [ 20 ]. An interesting example where a consistent effect is observed across diverse host strains is the plasmid pLL35, which causes the upregulation of bacterial anaerobic metabolism genes in phylogenetically diverse E. coli backgrounds [ 28 ]. Although the effect on bacterial growth is unknown, it is possible that by shifting the host cell from aerobic towards anaerobic metabolism, the plasmid may potentiate gut colonization, and thereby promote the fitness of both the bacterium and the plasmid in this niche.…”
Section: Linking Altered Expression Of Bacterial Functions To Plasmid Fitnessmentioning
confidence: 99%
“…Plasmid persistence is generally expected to depend on the balance of growth costs (how plasmids affect bacterial population growth) and transfer rates (typically by conjugation) and, to a lesser extent given many natural plasmids carry addiction systems, segregational loss (Stewart and Levin, 1977; Levin et al ., 1979; Finbarr, 1995; Ponciano et al ., 2007; San Millán et al ., 2014). Past work showed growth costs (Alonso-del Valle et al ., 2021; Dunn et al ., 2021), transfer rates (Lopatkin et al ., 2017; Sheppard et al ., 2020) and segregational loss (De Gelder et al ., 2007) can vary depending on the bacterium-plasmid combination. This variability may therefore be central to predicting the long-term stability of plasmids (over hundreds of generations and in the absence of antibiotics).…”
Section: Introductionmentioning
confidence: 99%
“…Ancestral WGS data are available under Bioproject Accession number PRJNA667580, and are described in (Dunn et al, 2021).…”
Section: Genomics and Bioinformaticsmentioning
confidence: 99%
“…Evolved plasmid-carrier clones were tested for their ability to conjugate pLL35 into an E. coli J53 recipient strain as previously described (Dunn et al 2021). Conjugation positive strains are demoted with "+" and conjugation deficient strains are denoted with "-".…”
Section: Table S3 | Conjugational Abilities Of Evolved Clonesmentioning
confidence: 99%